Effects of a Two-Way Bilingual Program on the Literacy Development of Students in Kindergarten and First Grade - López, María G.; Tashakkori, Abbas (Bilingual research journal, 2004)
This study examines the short-term effects of a two-way bilingual education program on the literacy development of students in kindergarten and first grade. This study compared the literacy development of two groups of children who received different proportions of instruction in English and Spanish. Both the experimental and control groups consisted of students who were English language learners (ELLs), as well as students who were not ELLs (i.e., native English speakers and former ELLs who reached proficiency). Students in the experimental group participated in a two-way bilingual program in which instruction was in English approximately 70% of the time and in Spanish approximately 30% of the time. Students in the control group attended the same school but were in mainstream classes and received instruction in English about 90% of the time. Comparison of test scores (on district-developed assessments and the Scholastic Reading Inventory) of the two groups at the end of the school year indicated that in spite of the initially lower pretest scores in some subject areas, the experimental group's achievement was very close to that of the control group. It is concluded that two-way bilingual programs can assist schools in improving ELLs' academic achievement in English language arts.